THE ROLE OF HEDONIC MOTIVATION IN SOCIAL COMMERCE TOWARD CONSUMER PURCHASE INTENTION - Kumaresan, Kumaran; Janifer, Lunyai; Nordiana, Ahmad Nordin (UNIMAS Publisher, 2024)
This study investigates the influence of Theory of Planned Behavior (TPB) and Technology Acceptance Model (TAM) elements on customer purchase intention within the context of social commerce, with a focus on the moderating role of hedonic motivation (HM). TPB factors, including attitude (ATD), subjective norm (SN), and perceived behavioral control (PBC), along with TAM factors - perceived ease of use (PEOU) and perceived usefulness (PU) - were examined for their connection to consumer purchase intention (CPI). Hedonic motivation's role as a moderator between TPB, TAM, and purchase intention was explored due to its impact on sensory, creative, and emotional responses of hedonic consumers towards products. The study, involving 500 online survey participants, employed SPSS 26.0 for initial analysis and Smart PLS 3.0 for structural equation modeling. Results supported seven out of ten hypotheses, offering valuable insights into hedonic motivation's regulatory effect on customer purchase intention in the realm of social commerce, contributing to a deeper understanding of this evolving market.